Lesions of the folds are not always ''atopic dermatitis''. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
Very few diseases affect in a chronic persistent way the flexural aspect of the knees. This is why the distribution of the lesions is included among the major diagnostic criteria of atopic dermatitis. As a matter of fact, more than the morphology of the lesions, their chronic localization on the flexural aspect of the knees is characteristic of atopic dermatitis. (...).